Rich Picture Analysis of MRT Jakarta Transit-Oriented Development (TOD) Business Ecosystem - Ardiansyah, Zulfadli; Marimin, Marimin; Indrawan, Dikky; Yurianto, Yurianto (Pandawan, 2025)
Transit-oriented development (TOD) aims to create added value by optimizing regions around transportation hubs. It emphasizes the integration of mass transit systems with non-motorized transport while reducing the use of motor vehicles through the development of dense, mixed-use areas. This research examines the role of MRT Jakarta Co. in building a business ecosystem that supports TOD area creation. The objective is to identify key stakeholders and strategies that influence TOD implementation. This research uses Soft System Methodology (SSM), with data collected from seven MRT Jakarta Co. employees and expert interviews. Rich Picture analysis is used to visualize the interactions and challenges in the system. The results show that collaboration among MRT Jakarta Co., developers, government, associations, and landowners is essential. Barriers include regulatory limitations, inconsistent policies, and funding constraints. The Rich Picture reveals a complex structure of roles, norms, and power dynamics that shape TOD success. The research concludes that regulatory support, stakeholder engagement, and clear coordination mechanisms are critical for effective TOD development. These findings can guide policymakers and urban planners in enhancing transit-based city planning.